Factors of BPD Deposit Interest Rate, Government Bank Deposit Interest Rate, Inflation Rate, Economic Growth (GDP), and Money Supply to the Rupiah Exchange Rate per US dollar in Indonesia for 2004 – 2021 Period - Elsyan Rienette Marlissa; Zefanya Raghuel Riris Mamengko (AIBPM Publisher, 2024)
The study aims to analyze the effect of the BPD Deposit Interest Rate Factor, Government Bank Deposit Interest Rate, Inflation Rate, economic growth, and money supply affecting the exchange rate of the rupiah per US dollar in 2004-2021 partially and simultaneously. The research method uses secondary data in the form of panel data and cross section for 18 years (quarterly data on 26 provinces in Indonesia). Literature survey research from BI, BPD, and BPS Center. Quantitative analysis method using multiple linear regression analysis tools. The results showed that (1) partially, the interest rate factor of Government Bank deposits, the money supply has a positive but insignificant effect on the exchange rate of the rupiah per US dollar. Regional Development Bank deposit interest rates, inflation rates, and economic growth have a negative but significant effect on the exchange rate of the rupiah per US dollar; and (2) simultaneously, the factors of interest rates on deposits of BPD, interest rates on deposits of Government Banks, inflation rates, economic growth, money supply have a significant effect on the exchange rate of rupiah per US dollar. An increase in interest rates on deposits of Government Banks and money supply, a decrease in interest rates on deposits of BPD, inflation rates, and economic growth will increase the exchange rate of rupiah (depreciated).